Penjadwalan Waktu Proyek Pembangunan Tempat Gym Menggunakan Metode CPM (Critical Path Method) - Yuliani, Novita; Az Zahra, Nabila Khairunnisa; Sutrisno, Sutrisno (Fakultas Teknik Universitas Tulang Bawang, 2024)
Project scheduling is a method of arranging a schedule of tasks to be carried out to realize or achieve certain goals, by filling in a table of the time needed to complete. Critical Part Method (CPM) is a program method that can calculate the time needed to complete all activities and determine which ones the project implementer should pay attention to to ensure they can be completed as planned. The purpose of this study is to identify the critical path to which critical activities are included, as well as evaluate the scheduling between the project owner's planned time and the duration of the planning outcome. In the construction project of a gym with a land area of 60m (5 x 12m) in Mustika Prakarsa Block C Housing, Cibalongsari Village, Klari District, Karawang Regency, 41371. The data collected from this study is research analysis shows that fast and normal time network lines A, B, C, D, F, I, J, K, L, activities include making water channels, digging foundations, installing foundations, ironing, laying hebel bricks, polishing, installing floor tiles, checking, overall finishing. So, the project scheduling time based on the CPM method is 124 days normal time and 91 days fast time to complete the project. Keywords: Critical Path Method, Project Development, Project Management, Scheduling.